Reductionism and Action Predicates - Dranseika, Vilius (Problemos, 2012)
This article aims at characterizing discussions within the analytic philosophy of action on reductionist and antireductionist approaches to ordinary action predicates. Two antireductionist arguments – both of them directed against the possibility of extensional equivalence of ordinary action predicates and scientific predicates – are identified as central in shaping the discussion, namely, the argument from multiple realizability and the argument from rationality constraints. The article ends with a short discussion of practical considerations which, together with theoretical prospects for the reduction of ordinary action predicates, delineate possible scenarios of retentive and eliminative theory change in action theory.
Keywords: action; philosophy of; reduction; elimination; multiple realization; rationality